2003
DOI: 10.1113/jphysiol.2003.038778
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates hyperplasia but not hypertrophy in immature ovine cardiomyocytes

Abstract: Rat and sheep cardiac myocytes become binucleate as they complete the 'terminal differentiation' process soon after birth and are not able to divide thereafter. Angiotensin II (Ang II) is known to stimulate hypertrophic changes in rodent cardiomyocytes under both in vivo and in vitro conditions via the AT1 receptor and intracellular extracellular regulated kinase (ERK) signalling cascade. We sought to develop culture methods for immature sheep cardiomyocytes in order to test the hypothesis that Ang II is a hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 66 publications
2
40
1
Order By: Relevance
“…The AT 1a R receptor is the predominant angiotensin II receptor subtype in the heart [46] and it plays a key role in mediating the myocardial trophic effects of angiotensin II [47], [48] stimulating both hypertrophy and/or hyperplasia. IGF-1 plays a major role in cardiac growth, stimulating cardiomyocyte hypertrophy and hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AT 1a R receptor is the predominant angiotensin II receptor subtype in the heart [46] and it plays a key role in mediating the myocardial trophic effects of angiotensin II [47], [48] stimulating both hypertrophy and/or hyperplasia. IGF-1 plays a major role in cardiac growth, stimulating cardiomyocyte hypertrophy and hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 plays a major role in cardiac growth, stimulating cardiomyocyte hypertrophy and hyperplasia. The immature mouse cardiomyocytes are capable of both proliferation and hypertrophy at E17.5 [48], [49]. Hence, it is likely that the increase in AT 1a R and IGF-1 mRNA levels in DEX exposed fetuses at E17.5 may be driving the increase in heart weight from its relatively small size at E14.5 back to normal by E17.5.…”
Section: Discussionmentioning
confidence: 99%
“…Sundgren and colleagues found that activation of ERK and PI3K by IGF-1, and ERK alone by angiotensin II, stimulates fetal sheep cardiomyocyte proliferation in vitro (Sundgren 2003a; Sundgren 2003b). The ERK cascade was also required for the in vitro hypertrophic effects of phenylephrine.…”
Section: Discussionmentioning
confidence: 99%
“…AII causes near-term fetal sheep cardiomyocytes to proliferate in culture, contrary to its hypertrophic effect in cultured neonatal rat cardiomyocytes (O’Tierney et al 2010; Sundgren et al 2003). In contrast, AII infusion in utero increases ovine heart growth via myocyte hypertrophy and maturation (Norris et al 2014; Sandgren et al 2015; Segar et al 2001).…”
Section: Regulatory Signals Associated With Birthmentioning
confidence: 96%
“…For instance, AII-induced fetal cardiac growth is dependent on its hypertensive effect (Sandgren et al 2015), despite causing fetal sheep cardiomyocyte proliferation in culture (Sundgren et al 2003). Similarly, the effects of cortisol depend on site of administration and fetal hemodynamic effects (Giraud et al 2006; Lumbers et al 2005; Reini et al 2008).…”
Section: Regulatory Signals Associated With Birthmentioning
confidence: 99%